Multiple meanings of history in restoration. Issue 5 (19th June 2021) - Case, Madelon F.; Hallett, Lauren M.
Abstract : In ecological restoration, the role of historical fidelity in restoration references has long been both a foundational concept and a frequent source of debate. However, this is not the only role that history plays. History in the sense of historical knowledge can inform goal‐setting and provide tools for success. History in the sense of historical events (what has happened in a place) in many ways determines the goals and trajectories of restoration, and to what extent a historical reference is knowable and applicable. Here, we discuss a conceptual framework for how these forms of "history" interact, and particularly the underappreciated ways in which historical events shape the aspirations and limitations of restoration. We propose that considering legacies of historical events in the who, when, and where of restoration will be crucial to informing appropriate restoration goals for the future.